Paritoṣa - Śukla, Durgeśa (Navabhārata Sāhitya Mandira, 2010)
Paritoṣa – Raṅga che soraṭhane – Kaṅku ane kanyā – Kôphī plījha- Plays based on social and mysterious theme
One-act plays. - In Gujarati-Schr
Keywords: One-act plays; Gujarati